Sistema web de geolocalización de búsqueda de alquiler de habitaciones para estudiantes de la UNAP Iquitos - 2019 - Lozano Maguiña, Gianmarco (2020)
The purpose of this thesis project is to determine the search efficiency of real estate of FISI-UNAP students who reside in rooms for rent in Iquitos - Peru 2019, for this reason a web system that uses geolocation is determined and implemented to locate the properties for rent; providing information on the location of the properties among other data. The web system is developed in HTML5 with CSS3 using the language of the PHP server, for the use of the system the internet and the GPS (Global Positioning System) of the mobile device will be mandatory, the system had a map as its main interface. This research work has a quantitative approach of an applicative type with descriptive level. The research design is of the quasi-experimental type; The instruments to collect the data necessary for the development of this research work were the surveys and the observation sheet. The data collected were processed in a computerized manner, using the statistical software SPSS. The data is organized and worked in tables and represented in graphs to facilitate its analysis. The analysis and interpretation of the information will be complemented by the use of the T-Student statistical test, concluding that the search for real estate with the geolocation web system is more efficient than the traditional method and 55.33% of surveys from a sample of 47 students of the faculty of systems engineering of the National University of the Peruvian Amazon, they evaluate the satisfaction of the use of the web system as good; achieving the research hypothesis at the end of the study: “If a real estate geolocation web system is implemented, then the search time for real estate of FISI-UNAP students residing in rooms for rent in Iquitos will be more efficient - Peru 2019 "